2007
DOI: 10.1080/10715760600944296
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of MnSOD interactions with nitric oxide: Nitric oxide dismutation and the generation of peroxynitrite and hydrogen peroxide

Abstract: The present study demonstrates that manganese superoxide dismutase (MnSOD) (Escherichia coli), binds nitric oxide (*NO) and stimulates its decay under both anaerobic and aerobic conditions. The results indicate that previously observed MnSOD-catalyzed *NO disproportionation (dismutation) into nitrosonium (NO+) and nitroxyl (NO-) species under anaerobic conditions is also operative in the presence of molecular oxygen. Upon sustained aerobic exposure to *NO, MnSOD-derived NO- species initiate the formation of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
3
34
0
4
Order By: Relevance
“…Recently it was shown that upon sustained aerobic exposure to NO., MnSOD-derived NO -initiates the formation of ONOO -which leads to ONOO -decomposition and ONOO -dependent enzyme tyrosine residue nitration, oxidation and partial MnSOD enzyme inactivation. 40 As in our experiments aloin decreased iNOS activity and consequently NO. production, such conditions may also be responsible for the increased activity of MnSOD compared to controls.…”
Section: Discussionsupporting
confidence: 49%
“…Recently it was shown that upon sustained aerobic exposure to NO., MnSOD-derived NO -initiates the formation of ONOO -which leads to ONOO -decomposition and ONOO -dependent enzyme tyrosine residue nitration, oxidation and partial MnSOD enzyme inactivation. 40 As in our experiments aloin decreased iNOS activity and consequently NO. production, such conditions may also be responsible for the increased activity of MnSOD compared to controls.…”
Section: Discussionsupporting
confidence: 49%
“…Activity for MnSOD is significantly reduced in EAD brain and CSF compared with the age-matched control, which is consistent with the concept of mitochondrial dysfunction as a factor in the progression of AD. MnSOD was also found to be nitrated and subsequently inactivated in mice by peroxynitrite (121,149). Overexpression of SOD2 increases Ab degradation, while partial deficiency promotes Ab deposition, thereby likely contributing to cognitive decline observed in a transgenic mouse model of AD (134).…”
Section: Ead Carbonylated Proteinsmentioning
confidence: 99%
“…Figure 3 shows the rapid increase in detectable signal from an NO-specific electrode when Cu,Zn SOD is incubated with Angeli's salt. Conversely, MnSOD, which forms a stable nitrosyl complex (46), releases NO much more slowly.…”
Section: Fig 3 Reactivity Of Hno With Cuzn Sod and Mnsodmentioning
confidence: 99%